Wicked bugs : the louse that conquered Napoleon's army & other diabolical insects - Stewart, Amy (Algonquin Books of Chapel Hill, 2011)
In this darkly comical look at the sinister side of our relationship with the natural world, Stewart has tracked down over one hundred of our worst entomological foes-creatures that infest, infect, and generally wreak havoc on human affairs.